2019
DOI: 10.1186/s12887-019-1825-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk-based approach to school entry examinations in Germany – a validation study

Abstract: BackgroundIn Germany, all preschoolers undergo a school entry examination (SEE). While most children are sufficiently served with standardized developmental tests only, for a small group of otherwise underserved children, the SEE should also include a subsidiary health checkup. The aim of the study was to validate selection criteria to differentiate these two groups of children.MethodsSecondary data from the SEEs of 2016 and 2017 that contained information on 3513 children were analyzed. Of these children, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Previous research has shown that the SEE can be a useful tool to identify children at higher risk of health issues and developmental delays [21][22][23].…”
Section: The School Entry Examinationmentioning
confidence: 99%
“…Previous research has shown that the SEE can be a useful tool to identify children at higher risk of health issues and developmental delays [21][22][23].…”
Section: The School Entry Examinationmentioning
confidence: 99%
“…In Germany, SEEs are obligatory examinations, where all children are examined by the respective communal departments of public health (Gesundheitsamt) in the year before starting school. These checkups comprise a parental questionnaire, a standardized examination including vision, hearing, and developmental tests, and a clinical examination by the public health physician that aim to detect developmental delays which could interfere with the child's educational success [35][36][37][38], obtain epidemiological data [37,[39][40][41] and provide individual medical help to children who are otherwise underserved [42][43][44].…”
Section: Datasetmentioning
confidence: 99%
“…In a German study, selection criteria such as low social status, missing the last paediatric routine check-up, migration background, and being raised by a single parent could differentiate children for whom school entry examination should include a health check by a physician from those with no need for one. 9 These criteria may be ethically more difficult to accept than criteria based on concerns regarding each child. Our previous research suggested that at least one in four children have no need for a health check by school doctor according to questionnaires that assess the concerns of parents, teachers, and nurses regarding each child’s physical, mental, and social health.…”
Section: Introductionmentioning
confidence: 99%
“…One issue still requiring solid evidence is whether school doctor services ought to be offered as universal health checks or as targeted interventions in response to the needs of a child. In a German study, selection criteria such as low social status, missing the last paediatric routine check-up, migration background, and being raised by a single parent could differentiate children for whom school entry examination should include a health check by a physician from those with no need for one 9. These criteria may be ethically more difficult to accept than criteria based on concerns regarding each child.…”
Section: Introductionmentioning
confidence: 99%